Ackermannviridae bacteriophage against carbapenem-resistant Klebsiella pneumoniae of capsular type 64 - Li, Juan; Feng, Yu; Luo, Huan; Fang, Qingqing; Yang, Yongqiang; Zong, Zhiyong (Frontiers in Microbiology, 2024)
Lytic bacteriophages (phages) are promising clinically viable therapeutic options against carbapenem-resistant Klebsiella pneumoniae (CRKP). In China, the predominant strains are those assigned to sequence type 11 and capsular type 64 (ST11-KL64). The emergence of phage resistance is a major bottleneck hindering effective phage therapy, requiring more new phages to provide the flexibility for creating different phage cocktails. However, the majority of phages against ST11-KL64 CRKP belong to the genus Przondovirus of the family Autographiviridae, which limits the options for constructing cocktails. We recovered a novel lytic phage of the genus Taipeivirus within the family Ackermannviridae against ST11-KL64 CRKP from a river in China. We phenotypically characterized this phage and obtained its genome sequence for analysis. This phage can inhibit the growth of ST11-KL64 CRKP for 6.5 h at a 0.1 multiplicity of infection and exhibits a narrow host range, being unable to attack CRKP strains of the other 30 capsular types. This phage carries no genes encoding antimicrobial resistance, virulence, or lysogeny. It is stable across a wide range of temperatures and pH values, making it suitable for phage therapy. Unlike other Taipeivirus phages, P01 has two tail spike proteins and a unique tail fiber protein. The distinct tail composition of this phage contributes to its activity against ST11-KL64 CRKP and its narrow host range. Taken together, we recovered a phage of a novel viral species with the potential for therapy, which expands the phage biobank against CRKP.